Out of the inkwell : Max Fleischer and the animation revolution - Fleischer, Richard (University Press of Kentucky, 2005)
Max Fleischer (1883-1972) was for years considered Walt Disney's only real rival in the world of cartoon animation. The man behind the creation of such legendary characters as Betty Boop and the animation of Popeye the Sailor and Superman, Fleischer asserted himself as a major player in the development of Hollywood entertainment. Out of the Inkwell: Max Fleischer and the Animation Revolution is a vivid portrait of the life and world of a man who shaped the look of cartoon animation. While deeply engaged with his characters, Fleischer also sought ways to improve his art through technical innova.